1993
DOI: 10.1002/bit.260410707
|View full text |Cite
|
Sign up to set email alerts
|

A statistical analysis of the effect of substrate utilization and shear stress on the kinetics of biofilm detachment

Abstract: One of the least understood processes affecting biofilm accumulation is detachment. Detachment is the removal of cells and cell products from an established biofilm and subsequent entrainment in the bulk liquid. The goal of this research was to determine the effects of shear stress and substrate loading rate on the rate of biofilm detachment. Monopopulation Pseudomonas aeruginosa and undefined mixed population biofilms were grown on glucose in a RotoTorque biofilm reactor. Three levels of shear stress and subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
85
2
2

Year Published

1996
1996
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(91 citation statements)
references
References 16 publications
2
85
2
2
Order By: Relevance
“…In most fixed biomass systems, stable and higher flow rates have the advantage of limiting biofilm growth (Peyton and Characklis, 1993;Melo and Vieira, 1999;Cloete et al, 2003), since they produce thinner and more cohesive layers less prone to release bacteria into the bulk water. However, these conditions are not always feasible to maintain in drinking water networks.…”
Section: Introductionmentioning
confidence: 99%
“…In most fixed biomass systems, stable and higher flow rates have the advantage of limiting biofilm growth (Peyton and Characklis, 1993;Melo and Vieira, 1999;Cloete et al, 2003), since they produce thinner and more cohesive layers less prone to release bacteria into the bulk water. However, these conditions are not always feasible to maintain in drinking water networks.…”
Section: Introductionmentioning
confidence: 99%
“…Detachment refers to the release of microbial cells and their associated matrix polymers from the biofilm to the bulk fluid bathing the film. Some of the factors that have been suggested to be important in biofilm detachment include matrix-degrading enzymes (1,3,14,30), microbially generated gas bubbles (16), nutrient levels and microbial growth status (2,12,18,22,23,25), availability of multivalent cross-linking cations (2,4,29), fluid shear stress (18)(19)(20)27), contact attrition (5), quorum-sensing signals (1,9), and the activation of a lytic bacteriophage (32).…”
mentioning
confidence: 99%
“…Most studies of detachment of microbial cells use biofilms formed under dynamic conditions in which detachment is induced by liquid flow. These studies have shown the influence of numerous factors on the detachment of bacterial cells, such as nutrient limitation (21,38,45), growth phase (38), growth rate (40, 41), shape of the microbial cells (20), and nature of the substrate material (20,40,46). Other authors have studied the transfer of bacterial cells simply deposited on a surface (36, 37).…”
mentioning
confidence: 99%